ORIENTATION IN A SIGNAL FLOW AND INTELLIGENCE OF CHILDREN WITH AUTISTIC SPECTRUM DISORDERS - Nikolaeva, Elena; Gaidamakina, Margarita; Zavodovskaia, Darja A. (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The hypothesis was tested that these children may be more effective than their normally developing counterparts when analyzing a signal flow unrelated to speech or social conditions, for example something that is Nature-based or abstract. There were 52 participants in the study: 22 children with autism spectrum disorders, ranging in age from 3.1 to 7.9 years old, and 30 normally developing children, who were 4-5 years old. In order to achieve the goals and objectives the following methodologies were used: the Sally-Anne test; reflexometry; Raven’s Colored Progressive Matrices; a parent questionnaire. Results. Out of the 22 preschool children with ASDs, 21 of them had an unformed theory of mind. In the norm group, 80 percent of the children had a formed theory of mind. Mute preschool children with ASDs made fewer mistakes in the simple sensory-motor reactions (of the go-go type). Mute children with ASDs were better at orienting themselves in a sensory flow that was unrelated to speech and social information, which can be considered as a compensatory reaction, given their psychophysical inability to develop normal speech. In mute children with ASDs, the level of nonverbal intelligence was no different from that of the children in the norm group.